3D Analysis of Human Movement, Sport, and Health Promotion - Petrigna, Luca (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The 3D analysis of human movement aims to objectively and quantitatively assess motor functions and alterations. It is a valuable method for sport scientists, coaches, and clinicians to evaluate sport performance, common movements, and alterations. The feasibility of 3D analysis is increasing because it can be adopted both in a laboratory setting or directly in the field, in static or dynamic conditions, and for physiological or pathological movements. This evaluation technique can be adopted for many people, including children, adolescents, adults, and older people, whether they are sedentary or athletes and whether they are healthy or motor-impaired people.